Tomografia computadorizada helicoidal com contraste hídrico com carcinoma gástrico: estadiamento tumoral pré-operatório e aspecto tomográfico dos tipos histológicos de Laurén - Ricardo Alexandre Fernandes Ferro (2007)
The therapeutic and prognostic definitions of the gastric carcinoma depend on an accurate diagnosis, histological classification and tumoral staging. Abdominal computerized tomography (CT) scan has been the most useful methodology employed on gastric carcinoma staging. It has also been applied, in some cases, on gastric carcinoma diagnosis and, rarely, on the histological type definition. In this study, 40 patients with gastric carcinoma had their tomographic, preoperatory and pathologic findings correlated, in order to assess their CT diagnostic indexes. We analyzed: tumoral location and staging, depth of gastric wall infiltration, lymph nodal metastasis and the presence of intra abdominal metastasis. Moreover, the capacity of water contrast CT in predicting Laurens histological type, even during the preoperatory phase, was also studied and the anathomic-pathologic results were considered gold-standard. Helical water contrast CT, in relation to the tumoral location, was able to define accurately the third (s) and curvature (s) / wall (s) affected in, respectively, 75% and 67.5% of the cases. The depth of gastric wall infiltration (T stage) was correctly identified by the CT in 86.6% of the cases, with a sensibility of 84% and a positive predictable value of 81.2%. The agreement between the tomographic and pathologic N stage was of 86.1%, with 91.2% of specificity. Helical TC accuracy on the definition on the T stage was higher than 87%, with 94.3% of sensibility and positive predictable value of 91.7%. The mean rate of increased attenuation post contrast was of 48H ± 6.9H for the intestinal type, 84H ± 9.1H for the diffuse and 87H ± 22.1H for the so-called nonclassified types. We did not observe any statistically significant difference between the diffuse and non-classified tumors. There was, however, a significant difference (p<0.0001) between the intestinal gastric carcinoma and the diffuse and non-classified tumors. According to this parameter, the abdominal CT correctly defined Laurens histological types in 100% of the diffuse carcinomas and in 88, 9% of the intestinal tumors. The sensibility on the histological diagnostic type was approximately 95%, with accuracy, specificity and predictable values higher than 90%. The mean thickness of the gastric wall was of 11.6 ± 8.8mm for the intestinal carcinoma and 22.7 ± 8.7mm for the diffuse one, with accuracy and sensibility of approximately 75% on the histological type definition. We concluded that helical water contrast CT presents good accuracy for gastric carcinoma staging and a great capacity for predicting Laurens histological types, allowing the differentiation of the intestinal carcinomas from the diffuse ones but not the diffuse types from Laurens non-classified ones.